Representation and object: A pyxis on the sarcophagus of Titus Aelius - Szántó, Virág Veronika (Dissertationes Archaeologicae, 2026)
The sarcophagus of Titus Aelius was found in 1989 during an excavation conducted by Sándor Petényi at Alsógalla. It stands out amongst sarcophagi depicting married couples for its refined execution and good state of preservation. However, what makes it particularly interesting is the depiction of the woman, who is shown holding a small, round object in her hand. This object was originally described as a jewellery box, but its form more closely resembles that of a perfume box. Building on an assessment of this find, the study evaluates the possibilities for comparing representations with extant objects and presents the results.